Il carteggio tra Luigi Schiaparelli e Carlo Cipolla (1894-1916) - olivieri, antonio (Reti Medievali E-Book, 2020)
More than four hundred letters and postcards remain of the long correspondence between Carlo Cipolla, born in Verona and professor of modern history in Turin and then in Florence, and Luigi Schiaparelli, one of the students from his time in Turin. The majority of the letters came from the student, on the grounds of communicative asymmetry and conservative accidents. There are over twenty years of epistolary dialogue (1894-1916) in this publication, which now contributes significantly to the knowledge of Schiaparelli (the first modern scholar of diplomacy and palaeography in Italy), his years of apprenticeship and his career début, as well as on the vicissitudes of the last years of Cipolla's career. Further insights are also gained on several aspects of the history of historical studies in Italy (and partly in Germany) in the decades between the 19th and 20th century, up to the World War I. The correspondence offers infinite, unpublished glimpses and lively accounts on people, events and discussions animating this intense season of Medieval Studies.